2010
DOI: 10.1136/ard.2010.129197
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic statins prevent matrix metalloproteinase-mediated cartilage collagen breakdown by inhibiting protein geranylgeranylation

Abstract: This study shows, for the first time, that lipophilic statins are able to block cartilage collagen breakdown induced by proinflammatory cytokines, by downregulating key cartilage-degrading enzymes. This demonstrates a possible therapeutic role for statins in acting as anti-inflammatory agents and in protecting cartilage from damage in joint diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 57 publications
3
27
0
1
Order By: Relevance
“…Here, we report a significant and apparently dosedependent reduction of PMA-stimulated release of MMP-9 by HUVECs treated with the lipophilic statins simvastatin and atorvastatin, but not by hydrophilic statin pravastatin. Our findings are in line with previous studies showing that simvastatin (Massaro et al 2010;Barter et al 2010;Corpataux et al 2005;Bellosta et al 1998;Luan et al 2003) or atorvastatin (Corpataux et al 2005;Souza-Costa et al 2007a;Souza-Costa et al 2007b) downregulate MMP-9 levels. Moreover, the lack of effects of pravastatin on net MMP-9 levels aligns with those reported by Hurks and colleagues (Hurks et al 2010), thus suggesting that significant differences exist in the effects exerted by different statins.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Here, we report a significant and apparently dosedependent reduction of PMA-stimulated release of MMP-9 by HUVECs treated with the lipophilic statins simvastatin and atorvastatin, but not by hydrophilic statin pravastatin. Our findings are in line with previous studies showing that simvastatin (Massaro et al 2010;Barter et al 2010;Corpataux et al 2005;Bellosta et al 1998;Luan et al 2003) or atorvastatin (Corpataux et al 2005;Souza-Costa et al 2007a;Souza-Costa et al 2007b) downregulate MMP-9 levels. Moreover, the lack of effects of pravastatin on net MMP-9 levels aligns with those reported by Hurks and colleagues (Hurks et al 2010), thus suggesting that significant differences exist in the effects exerted by different statins.…”
Section: Discussionsupporting
confidence: 95%
“…Moreover, the lack of effects of pravastatin on net MMP-9 levels aligns with those reported by Hurks and colleagues (Hurks et al 2010), thus suggesting that significant differences exist in the effects exerted by different statins. Other studies support the idea that some, but not all statins, may downregulate MMPs, and give further support to the lack of major effects exerted by pravastatin on MMPs levels (Barter et al 2010;Ikeda et al 2000).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…vitro and in vivo studies demonstrated that statins inhibit production of inflammatory cytokines induce apoptosis in variety types of cells and inhibit Matrix Metalloproteinase (MMP)-1, -2, -3 and -9 production and activation 4 . Taken together, statins attenuate production of pro-inflammatory cytokines, inhibit MMP activation and induce apoptosis in variety types of cells 5 .…”
Section: Original Articlementioning
confidence: 99%